Apostles of Reason: The Crisis of Authority in American Evangelism, by Molly Worthen - Caufield, Catherine L. (Religious studies and theology, 2013)
Apostles of Reason: The Crisis of Authority in American Evangelism, by Molly Worthen. Oxford University Press, 2014. 352 pp., $27.95 ISBN-13: 9780199896462.